THE HELL with questions - Ippolito, Michela (Proceedings of the Amsterdam Colloquium, 2022)
We discuss previous accounts of wh-the-hell questions, highlighting the challenges these accounts face and propose a novel analysis that has the potential to extend to wh-the-hell questions crosslinguistically.